Analisis Dampak Kegemaran Menonton Film Drama Korea terhadap Remaja di Tangerang Selatan - Baskoro, Muhammad; Sukmayanti, Zanastia (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2025)
Korean dramas or Drakor are favored by Indonesian teenagers because they have their own charm. Drakor are a medium of learning and entertainment for teenagers. However, drakor also have a negative impact when watching excessively. This study aims to determine the positive and negative impacts of teenagers who like to watch drakor. The method used is descriptive quantitative and a sample of 25 Al-Azhar BSD high school students. The results showed that teenagers who liked watching drakor movies were 15 students (60%). Most students feel the benefits of increasing Korean vocabulary as many as 12 students (80%). The negative impacts that arise are staying up late more often as many as 8 students (53.3%), rarely doing assignments, and watching as many as 5 students (33.3%). It can be concluded that Drakor have many impacts on teenagers' lives. It is hoped that teenagers can watch drakor not excessively, limit the maximum daily screen time, deepen vocabulary and insight into Korean culture without setting aside Indonesian culture.